The Development of Case-Based Module to Improve Students Learning Outcomes in Citizenship Education - Sistriana Sistriana; Aunurrahman Aunurrahman; Andy Usman (JETL (Journal of Education, Teaching and Learning), 2019)
This study aims to determine the development of case-based modules through a module-based design development case material on Diversity of Tribes, Religion, Race and Intergroup in the Frame of Bhinneka Tunggal Ika, and to see how the implementation and acquisition of learning using case-based modules with research subjects of class VIII students who have studied the material. The research method used in this study is a development research method by combining Borg & Gall's development model with the Dick & Carrey learning design model. Data obtained through interviews, observations and tests applied to the subject of the study. The flow of this research is carried out through three main stages, namely (1) Product development plan phase, which includes analysis of learning objectives, learning analysis, identification of student characteristics, formulating objectives and planning of learning media, (2) Stage of product development, which includes product development, developing test instruments, developing learning strategies, developing and selecting instructional materials, designing and developing evaluation drafts, revising learning packages, and (3) testing and revision stages, which include small group trials, initial product revisions, medium scale tests, revisions second test of result product, and large-scale trials. The results showed a high percentage of the feasibility of learning activities, namely 84.26% in teacher activities and 83.33% in student activities. Learning gain that can be achieved by using case-based modules is the activity of students in learning activities and an increase in the percentage of mastery learning in the pretest and posttest implementation, from 20% to 46.67%. And viewed from the aspect of increasing understanding of the attitudes that must be had regarding the diversity of tribes, religions, races, and intergroup obtained through assessment instruments attitudes as a whole reached an average of 4, which means that some students consider each aspect important to ethnic diversity, religion, race, and intergroup.